2017
DOI: 10.1016/j.cie.2016.12.037
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of formulations for the capacitated lot sizing problem with setup crossover

Abstract: The lot sizing problem with setup crossover is an extension of the standard big bucket capacitated lot sizing problem (CLSP). The general idea is that the first setup operation of each planning period can already start in the previous period, if not all the capacity is used in that previous period. This provides more flexibility in the planning and increases the possibility of finding feasible and better solutions compared to the standard assumption. Two different formulations have been presented in the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…The setup structure in the capacity constraint is another consideration that affects the problem complexity ( Karimi et al, 2003 ). The setup of a product can be dependent or independent of the previous product in the production sequence ( Guimarães, Klabjan, & Almada-Lobo, 2014 ), or the final setup in a period can be carried over to the next period ( Gopalakrishnan, Ding, Bourjolly, & Mohan, 2001;Sahling, Buschkühl, Tempelmeier, & Helber, 2009 ) or split between two periods ( Fiorotto, Jans, & de Araujo, 2017 ).…”
Section: Discussion Of the Lot-sizing Problemmentioning
confidence: 99%
“…The setup structure in the capacity constraint is another consideration that affects the problem complexity ( Karimi et al, 2003 ). The setup of a product can be dependent or independent of the previous product in the production sequence ( Guimarães, Klabjan, & Almada-Lobo, 2014 ), or the final setup in a period can be carried over to the next period ( Gopalakrishnan, Ding, Bourjolly, & Mohan, 2001;Sahling, Buschkühl, Tempelmeier, & Helber, 2009 ) or split between two periods ( Fiorotto, Jans, & de Araujo, 2017 ).…”
Section: Discussion Of the Lot-sizing Problemmentioning
confidence: 99%
“…Ramya et al [7] proposed a formulation for the CLSP with setup carryover and setup-splitting and no backorders or lost sales. Fiorotto et al [12] compared two formulations proposed by Mohan [10] and by Menezes [6] and proposed symmetry braking constraints. With computational experiments, they showed that the proposed constraints are effective for the formulation proposed by Mohan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Constraints (11) ensure that remaining setup times are allowed only during setup crossover. From Assumption 1, idle time is not allowed during setup operation, this is reflected in constraints (12). First two terms of the left-hand side are added to lift the constraint.…”
Section: Variablesmentioning
confidence: 99%
“…(2016); Fiorotto et al. (2017) also studied the capacitated lot‐sizing problem with characteristics of setup carryover, crossover, and splitting. While considering the problem characteristics, they also propose MIP formulations and present their analyses.…”
Section: Literature Reviewmentioning
confidence: 99%